Factors affecting farm mechanization a case of rice production in Tanauan, Leyte - Castañeda, Jerrica P.; Fermano, Lady Jane A.; Magdalaga, Ana Rose R.; Risos, Marjorie M.; Pormon, Miah Maye M. (2016)
This paper determined the factors affecting the decision of selected rice farmers in adopting farm machineries in 22 barangays of Tanauan, Leyte. The study also included the socio-economic profile, machineries utilized, and the perceived advantages and problems of the farmer respondents. Data collected were analyzed using descriptive statistics, and binary logistic regression to determine the significant factors. Most of the farmers use tractors and thresher for land preparation and harvesting stage, while some also use water pumps for irrigation. Adoption of machinery is generally perceived to be advantageous by the respondents due to its time and labor-saving property, however, some find its relatively high cost of utilization a bit disadvantageous. Furthermore, majority of the respondents preferred to adopt farm machineries in order to improve the timeliness of their operations. Results also showed that irrigation, farm experience and contact with extension agent are the significant factors that influence the decision of farmers to adopt farm machineries. Moreover, the results of the study emphasized that greater efforts should be made to provide the farmers with better-quality irrigational facilities for them to be motivated to employ farm machinery innovations which could augment their rice produce. Furthermore, the researchers recommend for an increase in the number of extension agents as well as the frequency of their visits to the community so as to promote better and faster information dissemination about farm technology innovation.
Undergraduate thesis (B.A.S.S. Economics) -- University of the Philippines, Tacloban.
Keywords: Social Sciences